Effect Of Chicken Manure And Volcanic Ash On The Growth And Production Of Shallot (Allium ascalonicum L.) And P Availability In Paddy Field - Ernitha Panjaitan (Cita konsultindo, 2023)
This study aims to determine the effect of applying chicken manure and volcanic ash on the growth and production of shallots (Allium ascalonicum L.) and P availability in paddy fields. This research was conducted in paddy field at Jln. Harmonika Baru Pasar II, Tanjung Sari Urban Village, Medan Selayang Sub-district, Medan with an altitude of ± 30 meters above sea level. This research was conducted from December 2019 to February 2020. This study used a Randomized Group Design (RAK) with 2 treatment factors. The first factor, chicken manure with 4 levels, namely: A0 = Control (without chicken manure), A1 = 3.75 kg/plot (10 tons/ha), A2 = 7.5 kg/plot (20 tons/ha) and A3 = 11.25 kg/plot (30 tons/ha). The second factor is volcanic ash with 4 levels, namely: V0 = Control (no volcanic ash), V1 = 1.88 kg/plot (5 tons/ha), V2 = 3.75 kg/plot (10 tons/ha) and V3 = 5.62 kg/plot (15 tons/ha). The results showed that the treatment of chicken manure doses up to a dose of 7.5 kg/plot significantly increased leaf length, number of bulbs, wet weight of bulbs/plant, wet weight of bulbs/plot, dry weight of bulbs/plant, dry weight of bulbs/plot, base saturation, C-Organic, soil pH, and soil P availability, but had no significant effect on soil CEC. The treatment of vulaknik ash dose had no significant effect on leaf length, number of tubers, wet weight of tubers/plant, wet weight of tubers/plot, dry weight of tubers/plant, dry weight of tubers/plot, soil CEC, base saturation, C-Organic, soil pH and P availability. The interaction between doses of chicken manure and volcanic ash had a significant effect on the wet weight of tubers/plot and dry weight of tubers/plot, but had no significant effect on leaf length, number of tubers, wet weight of tubers/plant, dry weight of tubers/plant, soil CEC, base saturation, C-Organic, soil pH and P availability.